THE RELATIONSHIP BETWEEN COMMUNITY BEHAVIOR IN WASTE MANAGEMENT AND THE INCIDENCE OF DENGUE HEMORRHAGIC FEVER IN INDONESIA: A SYSTEMATIC REVIEW : COMMUNITY BEHAVIOR IN WASTE MANAGEMENT - Salsabila Syafni Aulia; Ratno Widoyo; Kamal Kasra (STIKes Mandala Waluya Kendari, 2026)
Background: Trash containers can potentially serve as breeding sites for mosquitoes that transmit dengue hemorrhagic fever. This study aims to examine the relationship between community waste management practices and the incidence of dengue hemorrhagic fever in Indonesia. Methods: A systematic review was conducted using the PRISMA approach on articles published between 2020 and 2025. Literature searches were performed using the PubMed, ScienceDirect, and Google Scholar databases, yielding five articles that met the inclusion criteria. Results: The findings indicate a significant association between community behavior in waste management and the incidence of dengue hemorrhagic fever. Communities that do not implement proper waste management practices are at a higher risk of developing dengue fever compared to those that do. Conclusion: Therefore, the application of the 3R principles (Reduce, Reuse, and Recycle) is strongly recommended to minimize potential breeding sites for Aedes aegypti mosquitoes.